Self-reported determinants for subjective financial distress: a qualitative interview study with German cancer patients - Eva Winkler; Katja Mehlis; Bastian Surmann; Wolfgang Greiner; Andrea Züger; Viktoria Mathies; Sophie Pauge; Luise Richter; Thomas Ernst; Natalja Menold (BMJ Open)
Objectives Patient-reported financial effects of a tumour disease in a universal healthcare setting are a multidimensional phenomenon. Actual and anticipated objective financial burden caused by direct medical and non-medical costs as well as indirect costs such as loss of income can lead to subjective financial distress. To better understand subjective financial distress, the presented study explores self-reported determinants for subjective financial distress in German patients with cancer, aiming to inform a new German-language patient-reported outcome measure for determining the financial effects of a tumour disease.Design Semistructured interviews with n=18 patients with cancer were conducted between May 2021 and December 2021. Patients were recruited based on a purposive sampling strategy in outpatient and inpatient settings. The interviews were audiorecorded, transcribed verbatim and analysed using qualitative content analysis.Setting Participants were recruited from two German academic cancer centres, that is, the National Center for Tumor Diseases Heidelberg and Jena University Hospital.Participants 18 patients who had undergone cancer-related therapy for at least 2 months were interviewed (10 females).Results Based on the results of the qualitative content analysis, we developed a multicomponent construct of determinants that could influence subjective financial distress. The self-reported determinants can be classified into material (savings, good salary, shared rent through shared living, employed partner, paid-off house, potential financial support from family and friends, work-related specifics, consumer restrictions, out-of-pocket-costs and anticipated financial changes), social (social support from friends and family), systemic (administrative hurdlers and insurance cover) and inner personal determinants (coping strategies, change of attitude, character traits).Conclusion Subjective financial distress depends not only on material but also on social, systemic and inner personal determinants. Knowledge of these determinants can inform a new comprehensive German-language instrument for measuring self-reported financial effects of a tumour disease.Trial registration number NCT05319925.